Comparison of Child Participation and Life Balance and Perceived Stress of Parents of Children on Dialysis with That of Normal Population. - Sheeba Parveen; Ruchi Nagar Buckshee (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Aim: The study compared child participation of children undergoing dialysis with that of normal population. Study design: comparative study design. Place and Duration of Study: This study was conducted in Sparsh Rotary south end charitable trust, Batra Hospital, New Delhi during year 2013-2015.Subjects and Methods:In this study design thirty children, fifteen children undergoing dialysis (5-18) years were recruited from Sparsh, Rotary south end charitable trust. And fifteen children without any problem were selected as per inclusion criteria. The participation in home-school and community of these children is measured using Child and Adolescent Scale of Participation (CASP and Life balance and perceived stress in caregivers was measured with Life Balance Inventory (LBI) and Perceived Stress Scale (PSS) respectively. The same scales were used for normal population. The scores was collected from each scale and statistically analyzed for both groups.Result:Results revealed that children on dialysis have less participation in home school and community with that of normal population. The perceived stress of caregivers of these children is also very higher and life balance score was found to be lesser when compared with caregivers of normal population.Conclusion:Clinical intervention of children undergoing dialysis is narrowed upon only medical intervention and not focuses more on participation. The Occupational Therapy intervention should be given to children undergoing dialysis.